The methodology and practice of econometrics : a festschrift in honour of David F. Hendry - Hendry, David F.; Castle, Jennifer; Shephard, Neil. (Oxford ; New York : Oxford University Press, 2009)
This book is a collection of papers dedicated to David F. Hendry (a seminal figure in modern econometrics) and his work. Many internationally renowned econometricians who have collaborated with Hendry or have been influenced by his research have contributed to this volume, which provides a reflection on the recent advances in econometrics and considers the future progress for the methodology of econometrics. Central themes of the book include dynamic modelling and the properties of time series data, model selection and model evaluation, forecasting, policy analysis, exogeneity and causality, and encompassing. The book strikes a balance between econometric theory and empirical work, and demonstrates the influence that Hendry's research has had on the direction of modern econometrics.
Includes bibliographical references and index.
lje 24/10/17
Loans
Keywords: Econometrics; Econometric models